Per3 length polymorphism in patients with type 2 diabetes mellitus - Karthikeyan, Ramanujam (2014)
BACKGROUND: A number of observations support the involvement of circadian clock genes in the regulation of metabolic processes. One of these circadian genes, Per3, exhibits a variable number tandem repeat length polymorphism, consisting of two alleles, namely four and five repeat alleles, in its exon 18. The objective of this study was to examine the existence of Per3 variants in patients with type 2 diabetes mellitus (T2DM) as compared to a non T2DM control group. METHODS: Intravenous blood samples were collected to obtain white blood cells from 302 T2DM patients and 330 non-diabetic, age- and sex-matched, individuals. Per3 genotyping was performed on DNA by polymerase chain reaction. RESULTS: Frequency of five repeat allele was higher, and that of four repeat allele lower, in T2DM patients as compared to non-diabetic controls (χ2=6.977, p=0.0082) CONCLUSIONS: The results indicate an association of Per3 five repeat allele with T2DM occurrence and suggest that individuals with five repeat allele may be at a greater risk for T2DM as compared to those carrying the four repeat allele.